Inhibitor repurposing reveals ALK, LTK, FGFR, RET and TRK kinases as the targets of AZD1480 - Gudernova, Iva; Balek, Lukas; Varecha, Miroslav; Kucerova, Jana Fialova; Kunova Bosakova, Michaela; Fafilek, Bohumil; Palusova, Veronika; Uldrijan, Stjepan; Trantirek, Lukas; Krejci, Pavel (Oncotarget, 2017)
Many tyrosine kinase inhibitors (TKIs) have failed to reach human use due to insufficient activity in clinical trials. However, the failed TKIs may still benefit patients if their other kinase targets are identified by providing treatment focused on syndromes driven by these kinases. Here, we searched for novel targets of AZD1480, an inhibitor of JAK2 kinase that recently failed phase two cancer clinical trials due to a lack of activity. Twenty seven human receptor tyrosine kinases (RTKs) and 153 of their disease-associated mutants were in-cell profiled for activity in the presence of AZD1480 using a newly developed RTK plasmid library. We demonstrate that AZD1480 inhibits ALK, LTK, FGFR1-3, RET and TRKA-C kinases and uncover a physical basis of this specificity. The RTK activity profiling described here facilitates inhibitor repurposing by enabling rapid and efficient identification of novel TKI targets in cells.